A method of reducing quenching residual stress in thick gauge martensitic steel
Patent Information
- Application Number
- CN202512027960.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-30
- Publication Date
- 2026-10-27
AI Technical Summary
[0008]本发明提供了一种降低厚规格马氏体钢淬火残余应力的方法,通过对合金中特定元素成分的调控设计,以优化相变过程,降低了中高碳合金钢经淬火获得全马氏体组织后内部残余应力,解决了因材料心部区域与表面区域换热能力差异导致的超高残余应力问题
[0026]1、源头性降低应力:通过成分设计直接干预马氏体相变的热力学条件(Ms点),从物理根源上降低了相变过程所产生的不均匀相变应变,降低了马氏体组织的相变残余应力,这是传统工艺优化无法实现的。
Smart Images

Figure CN122979761A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of heat treatment technology for metallic materials, and in particular to a method for reducing residual stress during quenching of thick-gauge martensitic steel. Background Technology
[0002] Martensitic steel is an important high-strength structural material, and obtaining a martensitic structure through quenching is key to achieving its ultra-high strength. However, martensitic phase transformation is accompanied by enormous volume expansion, and during quenching, a significant temperature difference exists between the surface and core regions of the workpiece, along with non-simultaneous phase transformation. The resulting superposition of thermal and structural stresses often leads to extremely high residual stress within the workpiece. This high residual stress severely reduces the fatigue strength of parts, promotes stress corrosion cracking, and can cause deformation or even cracking during subsequent processing or service. For thick workpieces, this problem is particularly pronounced because heat is difficult to dissipate from the core region.
[0003] During the continuous cooling process of phase transformation materials, the surface and edges of the martensitic steel strip cool first, experiencing tensile stress. Once the surface temperature reaches the phase transformation initiation temperature, the surface and edges of the strip begin to undergo phase transformation under tensile stress, generating positive phase transformation plastic strain. This causes the surface stress of the strip to gradually transform from tensile stress to compressive stress. Due to the self-balancing nature of residual stress, the stress in the core of the strip also gradually transitions from compressive stress to tensile stress along with the change in surface stress. When the core temperature reaches the phase transformation initiation temperature, the core begins to undergo phase transformation under tensile stress, generating positive phase transformation plastic strain. This causes the core stress to gradually transform from tensile stress to compressive stress, simultaneously driving the surface stress to transform from compressive stress to tensile stress.
[0004] If the thickness of the martensitic steel sheet is too large and its thermal conductivity is low, the cooling rate of the core will be low, resulting in a difference in microstructure between the core and the surface. In this case, the effect of phase transformation plasticity on residual stress will also change. At the beginning of cooling, the core of the steel sheet is under compression, while the surface is under tension. When the core temperature reaches the ferrite-pearlite phase transformation temperature, the core microstructure undergoes a phase transformation under compressive stress, producing negative phase transformation plastic strain. When the surface temperature reaches the martensitic phase transformation temperature, the surface undergoes a martensitic transformation under tensile stress, forming positive phase transformation plastic strain. Since the direction of the phase transformation plastic strain in the core is opposite to that on the surface, the superimposed effect will create considerable residual stress in the strip.
[0005] Existing technologies primarily reduce residual stress by optimizing the quenching process (such as staged quenching and isothermal quenching) or by performing subsequent tempering. For example, Chinese patent application CN114134292A, "A heat treatment process for controlling and preventing quenching cracks in thick-section 718H pre-hardened plastic mold steel," attempts to reduce temperature differences through complex temperature control. These methods require sophisticated equipment, have a narrow process window, and limited effectiveness. Patent CN102312060A, "An isothermal quenching method for G55SiMoV bearing steel," focuses on improving the properties of the quenching fluid. These methods all intervene from the external heat transfer process and fail to address the intrinsic cause of the high-stress characteristics of the martensitic phase transformation itself.
[0006] Traditional martensitic steel composition design (such as 40Cr and 42CrMo) aims to improve hardenability and ensure martensite formation in the core region, primarily through the addition of elements like Cr, Mo, and Mn. However, while improving hardenability, this design often increases the material's "quenching stress sensitivity." Higher hardenability means that more intense phase transformations may occur simultaneously or sequentially within a larger cross-section. If this sequential volume expansion cannot be coordinated, it can exacerbate stress.
[0007] Therefore, there is an urgent need for a new composition design approach that, while ensuring complete hardening, actively "passivates" the martensitic phase transformation process to achieve a synergy between "high strength" and "low internal stress". Summary of the Invention
[0008] This invention provides a method for reducing residual stress after quenching thick-gauge martensitic steel. By controlling and designing the composition of specific elements in the alloy to optimize the phase transformation process, the internal residual stress of medium- and high-carbon alloy steel after quenching to obtain a fully martensitic structure is reduced, solving the problem of ultra-high residual stress caused by the difference in heat transfer capacity between the core and surface regions of the material. Specifically, this is achieved through the following techniques.
[0009] This invention provides a method for reducing residual stress during quenching of thick-gauge martensitic steel. By synergistically controlling the content of carbon, manganese, nickel, and niobium, the martensitic transformation temperature is reduced, avoiding ferrite or bainite transformation in the core of the steel plate. This reduces the uneven transformation strain in different regions of the material during the transformation process, prevents stress concentration, and reduces non-coordinated strain.
[0010] Furthermore, by increasing the content of carbon, manganese, and nickel, the martensitic transformation temperature is lowered, thus suppressing the ferrite or bainite transformation in the core of the steel plate.
[0011] By controlling the niobium content to a trace level, the original austenite grains were refined, which in turn refined the size of the martensite lath bundles, dispersed the phase transformation stress, and prevented stress concentration. Niobium carbonitrides can also act as carbon traps, fine-tuning the local carbon activity and indirectly affecting the martensitic phase transformation behavior.
[0012] Furthermore, by coordinating the content of each chemical element in the martensitic steel, the martensitic phase transformation initiation temperature Ms in the martensitic steel is ≤300℃.
[0013] Furthermore, by mass percentage, the chemical composition of the martensitic steel includes 0.15%-0.35% C, 1.8%-3.0% Mn, 1.0%-2.5% Ni, 0.01%-0.05% Nb, with the balance being Fe and unavoidable impurities, and the total content of hardenable elements is ≤2.0%.
[0014] Specifically, by mass percentage, the chemical composition of the martensitic steel includes 0.17% C, 2.2% Mn, 0.8% Ni, 0.03% Nb, with the balance being Fe and unavoidable impurities.
[0015] To address the problem of excessive residual stress in the core region of existing medium- and high-carbon alloy steels after quenching, especially in thick workpieces, this invention provides a novel method for reducing residual stress after quenching of thick martensitic steels. Through the special design and synergistic effect of various alloying elements, while ensuring complete hardenability, the method actively reduces the intensity of martensitic phase transformation and promotes the self-tempering effect, ultimately significantly reducing residual stress after quenching from the perspective of the material's inherent properties.
[0016] The synergistic mechanism of the elements provided by this invention is as follows:
[0017] (1) The addition of C, Mn, and Ni reduces the Ms point: The synergistic effect of higher C, Mn, and Ni content can significantly reduce the martensitic transformation initiation temperature (Ms) to 300℃ or even lower. Reducing the Ms point is the key to reducing quenching stress. When the Ms point is very low, the martensitic transformation occurs in the stage where the overall temperature of the workpiece is already low and the temperature difference between the surface region and the core region is small. At this time, the overall temperature difference of the material is small, which inhibits the ferrite or bainite transformation in the core of the steel plate, improves the non-uniform transformation strain generated during the transformation process, reduces non-uniform plastic deformation, and thus effectively suppresses the generation of high stress.
[0018] (2) Addition of micro Nb: On the one hand, Nb refines the original austenite grains during austenitization, thereby refining the final martensite lath bundle size. The finer martensite substructure can disperse the phase transformation stress and prevent stress concentration. On the other hand, Nb carbonitrides may act as carbon traps during the phase transformation process, fine-tuning the local carbon activity and indirectly affecting the phase transformation behavior.
[0019] Furthermore, the chemical composition of the martensitic steel, by mass percentage, also includes a Si content of 0.2%-1.5%.
[0020] Specifically, the chemical composition of the martensitic steel, by mass percentage, also includes a Si content of 1.0%.
[0021] Furthermore, after austenitization (i.e., the heat treatment process after hot rolling, in which the material is re-austenitized through heat treatment), water-medium quenching is employed.
[0022] In the method provided by this invention, the role of Si is to suppress cementite precipitation and to promote the retention of carbon in defects such as dislocations after the martensitic phase transformation, thereby creating conditions for possible subsequent self-tempering effects.
[0023] The present invention also provides a thick-gauge martensitic steel with low quenching residual stress, wherein the chemical composition of the martensitic steel, by mass percentage, includes 0.15%-0.35% C, 1.8%-3.0% Mn, 1.0-2.5% Ni, 0.01-0.05% Nb, with the balance being Fe and unavoidable impurities.
[0024] Furthermore, the chemical composition of the martensitic steel also includes a Si content of 0.2%-1.5%.
[0025] Compared with the prior art, the advantages of the present invention are:
[0026] 1. Reduce stress at the source: By directly intervening in the thermodynamic conditions (Ms point) of martensitic phase transformation through composition design, the non-uniform phase transformation strain generated during the phase transformation process is reduced from the physical source, and the residual stress of phase transformation in martensitic structure is reduced, which cannot be achieved by traditional process optimization.
[0027] 2. Balancing high strength and low stress: While ensuring ultra-high strength through C content and full hardenability, it achieves a significant reduction in residual stress level, resolving the technical contradiction that it is difficult to achieve both simultaneously.
[0028] 3. Improve the safety of thick-section workpieces: It is especially suitable for high-strength structural parts with large cross-sections and thick specifications, which can effectively reduce the tensile stress level in the core area and greatly improve the fatigue resistance and delayed fracture resistance.
[0029] 4. Good process compatibility: The composition design is suitable for existing quenching processes, and even allows the use of media with slightly lower cooling intensity (such as oil quenching or high-speed air quenching), reducing the risk of quenching cracking and simplifying process control. Attached Figure Description
[0030] Figure 1 The images show the metallographic regions (b) and (a) of the martensitic steel before and after chemical composition adjustment in Example 1.
[0031] Figure 2This is an example of the changes in residual stress in the core and edge regions of martensitic steel before and after chemical composition adjustment in Example 1. Detailed Implementation
[0032] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0033] The method for reducing residual stress in thick-gauge martensitic steel after quenching provided in this embodiment is based on the core technology of adding carbon (C), manganese (Mn), nickel (Ni) and micro-niobium (Nb) to achieve the synergistic effect of "reducing the martensitic phase transformation temperature (Ms point)" and "promoting carbon diffusion during the phase transformation", thereby softening the phase transformation process and reducing non-coordinated strain.
[0034] Specifically, by increasing the content of carbon, manganese, and nickel, the martensitic phase transformation temperature was lowered; by controlling the niobium content to a trace level, the original austenite grains were refined, which in turn refined the size of the martensite lath bundles, dispersed the phase transformation stress, and prevented stress concentration; niobium carbonitrides can also act as carbon traps, fine-tuning the local carbon activity and indirectly affecting the martensitic phase transformation behavior.
[0035] Optionally, the chemical composition of martensitic steel, by mass percentage, includes 0.15%-0.35% C, 1.8%-3.0% Mn, 1.0%-2.5% Ni, 0.01%-0.05% Nb, with the balance being Fe and unavoidable impurities, and the total content of hardenable elements is ≤2.0%.
[0036] Optionally, in addition to the above chemical composition, the chemical composition of martensitic steel also includes a Si content of 0.2%-1.5%.
[0037] Example 1
[0038] The martensitic steel provided in this embodiment is used as an example to produce high-strength steel with a tensile strength ≥1100 MPa. Its chemical composition includes C: 0.17%, Mn: 2.2%, Ni: 0.8%, Nb: 0.03%, Cr: 0.22%, Mo: 0.3%; it is hot-rolled and quenched using standard processes.
[0039] Metallographic images of the core and surface regions of martensitic steel after quenching are shown below. Figure 1 As shown, the martensite content in the core region is >95%, and the maximum residual tensile stress in the core region is 350 MPa.
[0040] like Figure 2As shown, compared with martensitic steel with traditional composition (C: 0.17%, Mn: 1.14%, V: 0.07%, Cr: 0.22%, Mo: 0.2%), the residual tensile stress in the core region of the martensitic steel prepared in this embodiment is reduced by about 40% at the same strength level, and the workpiece does not crack during subsequent grinding.
[0041] Example 2
[0042] The martensitic steel provided in this embodiment is also taken as a high-strength steel with a tensile strength ≥1100 MPa. Its chemical composition includes C: 0.17%, Mn: 2.2%, Ni: 0.8%, Nb: 0.03%, Si: 0.4%, Cr: 0.22%, Mo: 0.3%. It is hot-rolled and quenched using standard processes to obtain the finished martensitic steel.
[0043] After quenching, the martensite content in the core region was also very high. Compared with the traditional composition (C: 0.17%, Mn: 1.14%, V: 0.07%, Cr: 0.22%, Mo: 0.2%), the residual tensile stress in the core region was significantly reduced at the same strength level, and the workpiece did not crack during subsequent grinding.
[0044] Therefore, by using the method of the present invention, by controlling the content of chemical components such as carbon, manganese, nickel, and niobium, ultra-high strength can be obtained through C content and full hardenability, while significantly reducing the residual stress of martensitic steel after quenching.
[0045] The above detailed embodiments describe the implementation of the present invention; however, the present invention is not limited to the specific details described in the above embodiments. Within the scope of the claims and technical concept of the present invention, various simple modifications and changes can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.
Claims
1. A method for reducing residual stress during quenching of thick-gauge martensitic steel, characterized in that, By synergistically controlling the content of carbon, manganese, nickel, and niobium, the martensitic phase transformation temperature is reduced, avoiding ferrite or bainite phase transformation in the core of the steel plate. This reduces the uneven phase transformation strain in different regions of the material during the phase transformation process, prevents stress concentration, and reduces non-coordinated strain.
2. The method for reducing residual stress after quenching of thick-gauge martensitic steel according to claim 1, characterized in that, By increasing the content of carbon, manganese, and nickel, the martensitic transformation temperature is lowered, thus suppressing the ferrite or bainite transformation in the core of the steel plate. By controlling the niobium content to a trace level, the original austenite grains were refined, which in turn refined the size of the martensite lath bundles, dispersed the phase transformation stress, and prevented stress concentration. Niobium carbonitrides can also act as carbon traps, fine-tuning the local carbon activity and indirectly affecting the martensitic phase transformation behavior.
3. The method for reducing residual stress after quenching of thick-gauge martensitic steel according to claim 1, characterized in that, In the martensitic steel, the martensitic phase transformation initiation temperature Ms ≤ 300℃.
4. The method for reducing residual stress after quenching of thick-gauge martensitic steel according to claim 1, characterized in that, The chemical composition of the martensitic steel, by mass percentage, includes 0.15%-0.35% C, 1.8%-3.0% Mn, 1.0%-2.5% Ni, 0.01%-0.05% Nb, with the balance being Fe and unavoidable impurities, and the total content of hardenable elements is ≤2.0%.
5. The method for reducing residual stress after quenching of thick-gauge martensitic steel according to claim 4, characterized in that, The chemical composition of the martensitic steel, by mass percentage, includes 0.17% C, 2.2% Mn, 0.8% Ni, 0.03% Nb, with the balance being Fe and unavoidable impurities.
6. The method for reducing residual stress after quenching of thick-gauge martensitic steel according to claim 4 or 5, characterized in that, The chemical composition of the martensitic steel, by mass percentage, also includes a Si content of 0.2%-1.5%.
7. The method for reducing residual stress after quenching of thick-gauge martensitic steel according to claim 6, characterized in that, The chemical composition of the martensitic steel, by mass percentage, also includes a Si content of 1.0%.
8. The method for reducing residual stress after quenching of thick-gauge martensitic steel according to claim 1, characterized in that, After austenitization, it is quenched in water.
9. A thick-gauge martensitic steel with low quenching residual stress, characterized in that, The chemical composition of the martensitic steel, by mass percentage, includes 0.15%-0.35% C, 1.8%-3.0% Mn, 1.0%-2.5% Ni, 0.01%-0.05% Nb, with the balance being Fe and unavoidable impurities.
10. The thick-gauge martensitic steel with low quenching residual stress according to claim 8, characterized in that, The chemical composition of the martensitic steel, by mass percentage, also includes a Si content of 0.2%-1.5%.
Citation Information
Patent Citations
Isothermal quenching method of bearing steel G55SiMoV
CN102312060A
Heat treatment process for controlling and preventing quenching cracking of thick and large-section 718H pre-hardening plastic die steel
CN114134292A